Preparation method of anti-deformation treating agent for plywood

By using a hybrid network of bio-based epoxy resin, polyols, and formaldehyde-free phenolic resin, the problem of deformation and impact resistance of plywood in humid environments has been solved, achieving high strength, high flexibility, and excellent water resistance. It is suitable for construction and furniture manufacturing and meets environmental protection standards.

CN121290559AActive Publication Date: 2026-01-09JIANGSU TUANYUAN HOME FURNISHING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511521979.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2026-01-09
Estimated Expiration
2045-10-23

AI Technical Summary

Technical Problem

Existing anti-deformation treatment agents for plywood have poor component synergy, making it impossible to simultaneously achieve high strength, high flexibility, and excellent water resistance. Furthermore, the preparation process is complex, energy-intensive, and difficult to maintain stability and safety in humid environments.

Method used

A hybrid fusion of bio-based epoxy resin, polyol, and formaldehyde-free phenolic resin was employed. Bio-based epoxy resin was prepared by the epoxidation reaction of soybean oil with hydroformic acid, bio-based polyol was prepared by the reaction of castor oil epoxy resin with triethanolamine, and formaldehyde-free phenolic resin was prepared by alkaline lignin glyoxal condensation. Chitosan catalyst and silane coupling agent were added to form a uniform hybrid network, thereby enhancing the deformation resistance of plywood.

Benefits of technology

It achieves anti-deformation, impact resistance, hydrophobicity and durability of plywood in humid environments, reduces warping and water absorption, meets environmental protection standards, is suitable for building and furniture manufacturing, and the preparation process has no volatile organic compound emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121290559A_ABST
    Figure CN121290559A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of chemical treatment agents, in particular to a preparation method of an anti-deformation treatment agent for plywood. The problem that an anti-deformation treatment agent is poor in anti-deformation durability is solved. Soybean oil is epoxidized through hydrogen peroxide and formic acid to prepare bio-based epoxy resin, an epoxy group of the bio-based epoxy resin and hydroxyl of wood cellulose are subjected to nucleophilic ring opening crosslinking to form a three-dimensional hydrogen bond network, meanwhile, a bio-based polyol flexible chain segment synthesized by castor oil epoxy resin and triethanolamine is fused, and the impact resistance and construction permeability are improved; and then fusing with formaldehyde-free phenolic resin obtained by catalytic condensation of alkaline lignin through glyoxal base to realize zero formaldehyde release and compatibility with plywood raw materials and enhance durable shear strength. During hybridization, a chitosan cationic catalyst is added to promote protonation ring opening of epoxy-phenolic hydroxyl groups and bonding of a silane coupling agent bridging interface, a uniform network is formed, warping and water absorption rate are reduced synergistically, and a water contact angle is increased. No volatile organic compound exists in the whole process, and plywood standards are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical treatment agent preparation technology, specifically a method for preparing an anti-deformation treatment agent for plywood. Background Technology

[0002] Plywood, a type of engineered wood product made by cross-linking multiple layers of veneers, is widely used in construction, furniture manufacturing, packaging, transportation, and interior decoration due to its excellent mechanical properties and controllable cost. However, the inherent hygroscopic nature of wood makes plywood susceptible to fluctuations in ambient temperature and humidity during use, leading to moisture absorption and expansion, and subsequent shrinkage and warping, cracking, blistering, and other deformation problems, severely reducing product lifespan and safety. To address this issue, the industry has developed various anti-deformation treatment agents for plywood, but current technology still faces significant bottlenecks.

[0003] In existing technologies, anti-deformation treatment agents are mainly divided into three categories: First, traditional amino resin-based treatment agents, represented by phenolic resin and urea-formaldehyde resin, enhance stability by strengthening the internal bonding strength of the board. However, these resins have high cross-linking density and high brittleness after curing, which cannot buffer the internal stress generated by the thermal expansion and contraction of wood. They also have insufficient water resistance and are prone to interfacial peeling under long-term high humidity. Second, epoxy resin-based treatment agents, although they have excellent bonding strength and chemical corrosion resistance, conventional solvent-based epoxy resins have problems with high VOC emissions and poor environmental performance, while water-based epoxy resins face defects such as poor emulsification stability and slow curing rate. Third, water-based polyurethane treatment agents, which have better flexibility and environmental performance, but when used alone, they have low cross-linking degree and insufficient durability of anti-deformation effect. They are prone to swelling failure under high temperature and high humidity conditions.

[0004] Furthermore, existing treatment agents generally suffer from poor component synergy: they either focus solely on strength enhancement while neglecting flexibility balance, or they improve water resistance at the expense of adhesion performance, making it difficult to achieve comprehensive optimization of anti-deformation, environmental friendliness, cost control, and ease of application. Simultaneously, some treatment agents have complex preparation processes, requiring high-temperature and high-pressure reaction conditions, resulting in high energy consumption and significant challenges in industrial scale-up. Therefore, developing an anti-deformation treatment agent for plywood with a rationally designed component synergy, a mild preparation process, and combining high strength, high flexibility, and excellent water resistance has become a pressing technical challenge in this field.

[0005] Therefore, a method for preparing an anti-deformation treatment agent for plywood is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing an anti-deformation treatment agent for plywood. Soybean oil is used to prepare a bio-based epoxy resin through a hydrogen peroxide and formic acid epoxidation reaction. The active epoxy groups of this resin undergo nucleophilic ring-opening crosslinking with the hydroxyl groups of wood cellulose to form a three-dimensional hydrogen bond network. Simultaneously, flexible segments containing tertiary amines and hydroxyl groups from a bio-based polyol synthesized from castor oil epoxy resin and triethanolamine through nucleophilic ring-opening are incorporated to buffer brittle fracture, improve impact resistance, and enhance construction penetration convenience. Further, it is fused with formaldehyde-free phenolic resin obtained by alkaline lignin condensation catalyzed by glyoxal, providing an environmentally friendly crosslinking scaffold, achieving zero formaldehyde release and polyurethane adhesive interface compatibility, and enhancing durable shear strength. The addition of a chitosan cationic catalyst in the hybrid fusion promotes the protonation and ring-opening of the epoxy-phenolic hydroxyl groups, while a silane coupling agent bridges the interfacial bonds, forming a uniform hybrid network that synergistically reduces warpage, water absorption, and increases the water contact angle. The entire green process is free of volatile organic compounds, meets plywood standards, and allows for multi-scale control of anti-deformation, impact resistance, hydrophobicity, and durability properties, making it suitable for manufacturing buildings and furniture in humid conditions.

[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing an anti-deformation treatment agent for plywood as follows: 80-120 parts of bio-based epoxy resin and 50-70 parts of bio-based polyol are added to a reaction vessel, stirred, and heated to 60-80°C. γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added to react and obtain an anti-deformation treatment agent precursor. Chitosan solution is added to the anti-deformation treatment agent precursor, followed by the dropwise addition of 130-170 parts of formaldehyde-free phenolic resin and deionized water. The temperature is raised to 70-90°C, and the pH is adjusted to 8-11. The reaction is then cooled to 35-50°C and filtered to obtain the anti-deformation treatment agent. In this invention, all "parts" refer to parts by weight. The cooling temperature range helps maintain the fluidity of the treatment agent for easy filtration, while avoiding excessively high temperatures that could cause emulsion demulsification or excessively low temperatures that could lead to a sharp increase in viscosity and blockage of the filter membrane. If cooled to room temperature, some high molecular weight components may precipitate, affecting product uniformity. Bio-based epoxy resin is obtained from soybean oil through an epoxidation reaction; Bio-based polyols are obtained from castor oil epoxy resin via a nucleophilic ring-opening reaction; Formaldehyde-free phenolic resin is obtained by alkaline lignin through alkaline catalytic condensation and reaction.

[0008] The preferred method for preparing bio-based epoxy resin is as follows: soybean oil and formic acid are mixed to form an emulsion system, hydrogen peroxide solution and concentrated sulfuric acid are added dropwise, and the reaction is carried out; after cooling, the organic phase is separated and washed, dried with anhydrous sodium sulfate, and distilled under reduced pressure to obtain bio-based epoxy resin; the CAS of soybean oil is 8001-22-7; The preferred method for preparing bio-based polyols is as follows: Castor oil epoxy resin, deionized water, and triethanolamine are mixed and heated with stirring; (tetrazolium-1,1,2,2-tetrahydrooctyl)trihydroxysilane is added dropwise under nitrogen protection, and the reaction continues with heating; after cooling, vacuum distillation is performed to obtain the bio-based polyol; the castor oil epoxy resin has an epoxy value of 0.38 mol / 100g; an average molecular weight of 933 g / mol; a viscosity of 300-500 mPa·s (25°C); and a density of 0.98 g / mL. Among them, (tridecylfluoro-1,1,2,2-tetrahydrooctyl)triethoxysilane is a silane coupling agent in which the ethoxy group in the molecule undergoes a hydrolysis reaction under acidic conditions, and the hydroxyl group in the water molecule replaces the ethoxy group to generate (tridecylfluoro-1,1,2,2-tetrahydrooctyl)trihydroxysilane, while releasing ethanol. Castor oil epoxy resin and deionized water are stirred evenly at 60°C to form a homogeneous dispersion system. Water serves as the dispersion medium to reduce the viscosity of the system. After the addition of triethanolamine, the pH of the system is maintained in an alkaline environment. The amino group in triethanolamine has a lone pair of electrons, which acts as a nucleophile to attack the electron-deficient carbon atom of the epoxy group. The strain of the epoxy ring makes it susceptible to nucleophilic attack and ring-opening reaction, generating a hydroxyl-containing intermediate. After most of the epoxy groups have completed ring-opening, the hydrolysis product is added. The silanol group and the hydroxyl group generated in the previous ring-opening reaction undergo a condensation reaction under alkaline conditions to form a silicon-oxygen-carbon bond, introducing the fluorosilicone segment into the polyol system.

[0009] Preferably, (tridecylfluoro-1,1,2,2-tetrahydrooctyl)trihydroxysilane is obtained by dissolving (tridecylfluoro-1,1,2,2-tetrahydrooctyl)triethoxysilane in ethanol, followed by hydrolysis and drying under acidic conditions; the CAS of (tridecylfluoro-1,1,2,2-tetrahydrooctyl)triethoxysilane is 51851-37-7.

[0010] A preferred method for preparing formaldehyde-free phenolic resin is as follows: Alkaline lignin and sodium hydroxide solution are mixed and stirred to dissolve; glyoxal aqueous solution is added dropwise; the mixture is heated to react; glyoxal aqueous solution is added again; the mixture is heated under nitrogen protection; the mixture is cooled to obtain formaldehyde-free phenolic resin; samples are taken every 30 minutes during the reaction, and the free glyoxal content is monitored using high-performance liquid chromatography (HPLC); the reaction endpoint is determined when the consumption rate is higher than 95%. The CAS number of alkaline lignin is 8061-51-6, with an average molecular weight of approximately 14,200 Da; phenolic hydroxyl content is 2.25 mmol / g; ash content is less than 5%; pH is 8.0-10.0; and degree of polymerization is approximately 50-100.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Bio-based epoxy resin is prepared using soybean oil as a raw material. At a suitable temperature, it reacts with hydrogen peroxide and formic acid to generate active epoxy groups, achieving a completely bio-based source and eliminating dependence on petrochemical raw materials. During plywood impregnation, the epoxy groups of the bio-based epoxy resin undergo nucleophilic ring-opening crosslinking with the hydroxyl groups of wood cellulose, forming a three-dimensional hydrogen bond network that blocks the active sites of the cellulose hydroxyl groups. This not only significantly reduces the warpage of the plywood but also improves its hydrophobic properties, decreasing water absorption and increasing the water contact angle, making it suitable for construction and furniture manufacturing in humid environments.

[0012] 2. Using castor oil epoxy resin as a raw material, a bio-based polyol is synthesized by reacting it with triethanolamine in an aqueous medium. Through the nucleophilic attack of the epoxy by the secondary amine, flexible polyether amine segments are introduced, forming a flexible structure. Incorporating this into the prepolymer as a chain extender effectively buffers the brittle fracture of the epoxy-phenolic network, significantly improving the impact resistance and strength of the plywood. Furthermore, this treatment agent has a moderate viscosity, facilitating vacuum impregnation, ensuring sufficient penetration depth, and making construction more convenient.

[0013] 3. Formaldehyde-free phenolic resin is prepared by reacting alkaline lignin with glyoxal at a high temperature. The reaction generates a prepolymer network that replaces traditional urea-formaldehyde resin, achieving zero formaldehyde release. Through the condensation of phenolic nuclei in the lignin phenylpropane units, an environmentally friendly cross-linking scaffold is provided, avoiding volatile organic compound emissions and an increased carbon footprint. When conventional polyurethane adhesives are used to glue and hot-press the treated veneers, the formaldehyde-free phenolic resin of this invention can form good hydrogen bonds and van der Waals forces at the polyurethane adhesive interface, exhibiting high shear strength, good compatibility, preventing interlayer separation, and significantly improved durability, making it suitable for sustainable furniture manufacturing.

[0014] 4. In the hybridization stage, this invention reacts bio-based epoxy resin, bio-based polyol, and formaldehyde-free phenolic resin at a suitable temperature. Simultaneously, chitosan is innovatively added as a cationic catalyst. The protonation of the amino groups in chitosan acts as a bridge, promoting the protonation and ring-opening of the hydroxyl groups in the epoxy phenol, significantly increasing the reaction rate and forming a uniform hybrid network. The silanol groups of the silane coupling agent also enhance the interfacial bonding between components, achieving multi-component synergy. The final treatment agent has a moderate solid content, neutral pH, and is stable during storage, making it suitable for industrial mass production. Plywood treated with this agent exhibits optimized resistance to deformation, impact, hydrophobicity, and durability. During construction, a uniform coating can be formed through dilution, impregnation, and hot pressing, making it economical and efficient.

[0015] 5. This invention integrates bio-based raw materials with a green synthesis pathway. The entire process generates no harmful substances such as formaldehyde or volatile organic compounds, fully complying with relevant plywood standards. Through the epoxidation of bio-based epoxy resin, ring-opening of bio-based polyols, condensation of formaldehyde-free phenolic resin, and catalytic fusion with chitosan, the hydroxyl groups of cellulose are blocked and cross-linked. From molecular-level cross-linking to enhance cohesion, to macroscopic-level flexible network balancing stiffness and toughness, multi-scale performance regulation is achieved. Attached Figure Description

[0016] Figure 1 The figures show the deformation and impact resistance test results of plywood treated with the deformation-resistant treatment agent in Examples 1-5 and Comparative Examples 1-4 of the present invention. Detailed Implementation

[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Please see Figure 1 This invention provides a method for preparing an anti-deformation treatment agent for plywood, the technical solution of which is as follows: Preparation Example 1 In a 500mL three-necked round-bottom flask equipped with a magnetic stirrer, dropping funnel, and thermometer, 100g of soybean oil and 15g of 85% formic acid were added. The flask was placed in an oil bath and stirred at 300rpm. The mixture was heated to 40℃ to form an emulsion. 120g of 30% hydrogen peroxide solution was slowly added dropwise at a rate of 2mL / min, while 0.5g of concentrated sulfuric acid was added simultaneously. The reaction temperature was gradually increased to 60℃, and the total reaction time was 4h. The endpoint of the reaction was determined by monitoring the disappearance of double bonds in the starting material using thin-layer chromatography. The volume ratio of petroleum ether to ethyl acetate was 4:1. The mixture was cooled to room temperature in an ice bath, and the organic phase was washed separately. The solution was dried with 20g of anhydrous sodium sulfate and distilled under reduced pressure at 60℃ and 0.1MPa to obtain a light yellow viscous liquid, which is the bio-based epoxy resin. The yield was 95g.

[0019] Preparation Example 2 Unlike the method in Preparation Example 1, the emulsion system was formed at a temperature of 35°C, the amount of concentrated sulfuric acid used was 0.3g, the reaction temperature was 50°C, and the yield was 92g.

[0020] Preparation Example 3 2 g of (tridecylfluoro-1,1,2,2-tetrahydrooctyl)triethoxysilane was dissolved in 5 mL of ethanol beforehand, and the pH was adjusted to 4 with 0.1 mol / L dilute hydrochloric acid to hydrolyze it into (tridecylfluoro-1,1,2,2-tetrahydrooctyl)trihydroxysilane. The hydrolysate was distilled under reduced pressure at 50 °C and 0.09 MPa until no obvious fraction was distilled off to remove ethanol and water.

[0021] In a 250 mL round-bottom flask equipped with nitrogen protection and magnetic stirring, 80 g of castor oil epoxy resin and 20 g of deionized water were added. The mixture was stirred at 400 rpm and heated to 60 °C until homogeneous. Subsequently, 10 g of triethanolamine was added under nitrogen protection at a flow rate of 50 mL / min. The temperature was raised to 80 °C and the reaction was allowed to proceed for 3 h. Then, (tetrazolium-1,1,2,2-tetrahydrooctyl)trihydroxysilane was slowly added dropwise to the system at a rate of 1 mL / min and the reaction was allowed to proceed for 15 min to form a fluorosilicone-epoxy premix. High-performance liquid chromatography (HPLC) showed that the epoxy group consumption was higher than 95%. The mixture was cooled to room temperature. The solvent and residues were removed by vacuum distillation at 70 °C and 0.05 MPa to obtain a transparent, viscous bio-based polyol with a yield of 100 g. The pH of the reaction was 9.

[0022] Preparation Example 4 Unlike Preparation Example 3, the pH of the silanol group obtained by hydrolysis was 5, and the pH was adjusted to 11 after the addition of triethanolamine; the yield was 98g.

[0023] Preparation Example 5 In a 250 mL three-necked flask equipped with a pH meter and a dropping funnel, 25 g of basic lignin and 85 mL of 1 mol / L sodium hydroxide were added. The mixture was stirred at 600 rpm and dissolved at room temperature for 30 min until a clear solution was obtained, at which point the pH was 13-14. 35 g of 40% glyoxal aqueous solution was slowly added dropwise at a rate of 1 g / min, and the temperature was gradually increased to 65 °C. The reaction was allowed to proceed for 30 min. 40 mL of 1 mol / L sodium hydroxide was added, and the temperature was increased to 90 °C. The reaction was carried out under nitrogen protection for 2 h, with the pH maintained at 11. The mixture was cooled to room temperature and distilled at 50 °C and 0.08 MPa for 45 min to obtain a brown prepolymer solution, i.e., formaldehyde-free phenolic resin. The yield was 150 g, with a solid content of 30%.

[0024] Preparation Example 6 Unlike Preparation Example 5, the amount of 40% glyoxal aqueous solution added was 40g, the reaction temperature was 70℃, the pH was maintained at 9 during the nitrogen protection process, the yield was 156g, and the solid content was 29%.

[0025] Preparation Example 7 Unlike Preparation Example 5, the amount of alkaline lignin was adjusted to 30g, and the amount of 1mol / L sodium hydroxide was adjusted to 95mL; the yield was 167g, and the solid content was 33%.

[0026] Example 1 In a 500 mL reactor equipped with mechanical stirring and temperature control, 100 g of the bio-based epoxy resin of Preparation Example 1 and 50 g of the bio-based polyol of Preparation Example 3 were added. The mixture was stirred at 300 rpm and heated to 70 °C. 2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added, and the reaction was carried out for 30 min until the pH of the system was 8. 0.5 g of chitosan was dissolved in 5 mL of 2% acetic acid and added to the system. 150 g of the formaldehyde-free phenolic resin of Preparation Example 5 was added dropwise at a rate of 5 g / min. 20 g of deionized water was added, and the temperature was raised to 85 °C at a rate of 2 °C / min. The reaction was carried out at 400 rpm for 2 h. During the reaction, the pH was adjusted to 9 with triethanolamine. The mixture was cooled to 40 °C and filtered through a 5 μm filter membrane to obtain a milky white anti-deformation treatment agent for plywood.

[0027] Examples 2-5 Except for the following adjustments to the preparation method, the other preparation methods are consistent with those in Example 1, as shown in Table 1.

[0028] Table 1. Preparation methods of anti-deformation treatment agents for plywood Comparative Example 1 Unlike Example 1, no bio-based polyols were added, the amount of bio-based epoxy resin was adjusted to 120g, and the amount of formaldehyde-free phenolic resin was adjusted to 180g.

[0029] Comparative Example 2 Unlike Example 1, no bio-based epoxy resin and formaldehyde-free phenolic resin were added, and the amount of bio-based polyol was adjusted to 300g.

[0030] Comparative Example 3 Unlike Example 1, instead of using a two-stage heating method, the temperature is directly heated to 85°C.

[0031] Comparative Example 4 Unlike Example 1, the reaction temperature was 95°C after adding formaldehyde-free phenolic resin, the pH was 11 during the reaction, and the reaction was finally cooled directly to room temperature.

[0032] Test Example 1 The bio-based epoxy resins, bio-based polyols, formaldehyde-free phenolic resins, and anti-deformation treatment agents for plywood prepared in Examples 1-7, Examples 1-5, and Comparative Examples 1-4 were tested for epoxy value, viscosity, hydroxyl value, and fluorine content, respectively. The test results are shown in the following content and Table 2.

[0033] The bio-based epoxy resins of Preparation Examples 1 and 2 had epoxy values ​​of 0.25 and 0.23 mol / 100g, respectively, and viscosities at 25°C of 451 and 423 mPa·s, respectively. The bio-based polyols of Preparation Examples 3 and 4 had viscosities at 25°C of 650 and 642 mPa·s, respectively, hydroxyl values ​​of 250 and 248 KOH / g, respectively, and fluorine contents of 2.6 and 2.5 wt.%, respectively. The formaldehyde-free phenolic resins of Preparation Examples 5-7 had viscosities at 25°C of 200, 209, and 221 mPa·s, respectively.

[0034] Under the conditions of Preparation Example 1 and Preparation Example 2, based on the Prilezhaev epoxidation reaction, the unsaturated double bonds of soybean oil undergo electrophilic addition with the performic acid generated in situ, selectively forming epoxy groups. Concentrated sulfuric acid is used as a Lewis acid catalyst to accelerate the formation of peracid. In Preparation Example 2, the temperature and catalyst dosage were reduced to slow down the side reactions but slightly decrease the efficiency. The electrophilic activity of the epoxy groups was ensured for subsequent ring-opening crosslinking of cellulose hydroxyl groups to form an anti-deformation network. The resulting product had good performance.

[0035] Bio-based polyols were prepared under the conditions of Preparation Examples 3 and 4. Through a nucleophilic ring-opening reaction, the secondary amine of triethanolamine attacked the epoxy group of castor oil epoxy resin to form a polyether-amine segment, introducing hydroxyl groups to buffer rigidity. The (tridecylfluoro-1,1,2,2-tetrahydrooctyl)triethoxysilane was pre-hydrolyzed to generate silanol groups, which were then silanized with epoxy / hydroxyl groups to form fluorine-enriched side chains that promoted surface migration. In Preparation Example 4, the pH was increased to promote ring-opening and enhance nucleophilicity. The introduced fluorine element was beneficial to the hydrophobic properties of the final anti-deformation treatment agent for plywood.

[0036] Formaldehyde-free phenolic resins were prepared under the conditions described in Examples 5-7. Alkali-catalyzed condensation combined with Cannizzaro autoreduction resulted in the formation of a hydroxymethyl intermediate through Mannich addition of glyoxal to the lignin nucleus, followed by reduction to generate a cresol network, eliminating the need for formaldehyde. NaOH promoted phenol anionization. Example 5 demonstrated efficient condensation at the standard molar ratio and pH. Example 6, by increasing the amount of glyoxal and the temperature, enhanced the addition but slightly increased the free residue. Example 7, by increasing the amounts of lignin and NaOH, improved the degree of polymerization. In summary, the bio-based epoxy resin, bio-based polyol, and formaldehyde-free phenolic resin obtained under the above conditions exhibited good basic properties.

[0037] Table 2. Test results of viscosity and solid content of anti-deformation treatment agent for plywood. Under the conditions of Examples 1-5, the viscosity of the anti-deformation treatment agent for plywood was in the range of 651-748 mPa·s, and the solid content was in the range of 44%-47%. Under the conditions of Comparative Example 1, the absence of polyols resulted in high solid content, increased viscosity, and increased risk of brittleness. Under the conditions of Comparative Example 2, both solid content and viscosity were reduced, with only low polyol content and weak crosslinking effect.

[0038] Test Example 2 The formaldehyde release of the anti-deformation treatment agents prepared in Examples 1-5 and Comparative Examples 1-4 was tested. The specific test method is as follows: High-performance liquid chromatography (HPLC) using the perforation method was employed. 25g of the treated plywood sample (crushed to 20-40 mesh) was placed in a 1L sealed extraction vessel, 40mL of distilled water was added, and extraction was carried out at 40℃ for 3 hours. After derivatization with acetylhydrazine, the formaldehyde content was determined by HPLC (C18 column, mobile phase acetonitrile-water, detection wavelength 365nm). The release amount (mg / m³) was calculated as (mass of formaldehyde in the extract / sample surface area) × air volume conversion factor. Each sample was tested in triplicate, and the average was taken. The test results are shown in Table 3. GB18580-2017 "Formaldehyde Release Limits in Wood-based Panels and Their Products for Interior Decoration and Renovation" (E1 level limit ≤ 0.124 mg / m³) applies.

[0039] Table 3. Formaldehyde Emission Test Results of Anti-deformation Treatment Agent Examples 1-5 show formaldehyde release of 0.03-0.06 mg / m³, far below the E1 limit, which is due to the core design of formaldehyde-free phenolic resin. The lignin-glyoxal condensation replaces urea-formaldehyde, avoiding the source of formaldehyde. The epoxy / polyol fusion does not introduce VOCs, and the chitosan / γ-(2,3-epoxypropoxy)propyltrimethoxysilane bridging optimization network is dense, inhibiting residual volatilization. Comparative Examples 1-4 released 0.07-0.12 mg / m³, slightly higher than the examples but still compliant. The defects were amplified by trace sources. For example, Comparative Example 1 had no polyol, high phenolic content led to uneven condensation, and residual glyoxal volatilized, resulting in brittle and easily released structures. Comparative Example 4 had incomplete Cannizzaro induction at high temperature (95°C) and strong alkalinity, resulting in glyoxal degradation producing trace formaldehyde, and rapid cooling caused unstable structures. Comparative Example 2 had a single polyol without cross-linking anchoring, and residual fluorosilicone hydrolysis resulted in trace release. Comparative Example 3 had abrupt heating with local overheating, resulting in poor residual sealing of 0.09 mg / m³. This group lacked synergy / process optimization, and the release increased by 20-140%, highlighting the necessity of overall component balance.

[0040] Test Example 3 The products of Examples 1-5 and Comparative Examples 1-4 were diluted with water at a ratio of 1:1 to prepare an impregnation solution. The veneer was vacuum impregnated at 0.08 MPa for 15 min, dried at 60°C for 2 h, and hot-pressed and cured at 120°C and 1.4 MPa for 5 min. The veneer of Examples 1-5 and Comparative Example 1 treated with the anti-deformation treatment agent was tested for deformation resistance and impact resistance. The specific testing method is as follows: Deformation resistance is expressed as warpage rate. A plywood sample with dimensions of 300mm × 300mm × 15mm was prepared and placed in a constant temperature and humidity chamber to simulate a humid environment (relative humidity 85%, temperature 25℃) for 72 hours. The maximum warpage height (mm) at the four corners of the sample was measured using a laser displacement sensor. The warpage rate (%) was calculated as (maximum warpage height / sample side length) × 100. Before testing, the sample was equilibrated at 23℃ and 50%RH for 24 hours. Impact resistance was assessed using the Charpy simply supported beam impact test. Plywood samples measuring 50mm × 10mm × 3mm with a notch depth of 2mm were used. Support spacing was 40mm, and a 2kg drop hammer was used from a height of 500mm. The absorbed impact energy (J) was recorded, and the impact strength (J / m²) was calculated as absorbed energy / cross-sectional area. Each sample was tested five times, and the average value was taken. The final results are shown in Table 4 and... Figure 1 As shown.

[0041] Table 4 Results of Deformation and Impact Resistance Tests The plywood treated under the conditions of Examples 1-5 all exhibited low warpage and high impact resistance. Under standard equilibrium ratios, epoxy groups and cellulose hydroxyl groups underwent ring-opening crosslinking to form a hydrogen bond network, phenolic resin provided a rigid scaffold, polyol flexible chains buffered expansion stress, and fluorosilicone side chain migration reduced surface energy. Two-stage heating ensured uniform penetration, and appropriate pH optimized the etherification rate to avoid localized over-hardening. This synergy resulted in a dense anti-deformation network and balanced impact toughness. In Example 2, increasing epoxy improved crosslinking density, blocked more cellulose-OH sites, and inhibited moisture adsorption. High lignin content enhanced the degree of polymerization, and pH 10 promoted nucleophilic attack, resulting in the lowest warpage. Examples 3-5 strengthened the rigid scaffold, improved deformation stability, and enhanced impact resistance by rationally adjusting the amount and yield of polyether-amine flexible segments, phenolic resin, and fluorine chains.

[0042] Comparative Example 1 shows that the lack of flexible chains leads to excessive cross-linking of epoxy-phenolic resin, forming a brittle network. Excessive expansion and warping increase the rigidity of the phenolic resin, amplifying impact crack propagation. This defect highlights the necessity of polyol buffering, resulting in severe performance degradation. Comparative Example 2 shows that the single flexible component lacks cross-linking anchoring; although fluorine chains are present, the network is loose, allowing moisture penetration and increasing warping. Impact strength is relatively high, but rigid support is lacking. Comparative Example 3 shows that a sudden temperature change causes rapid and uneven component reaction, with localized over-cross-linked / unreacted areas coexisting, affecting uniformity and moderately reducing performance. Comparative Example 4 shows that high temperature and high pH promote degradation and secondary condensation, leading to network instability and increased warping. Rapid cooling freezes the uneven structure, causing impact cracks. These results demonstrate the necessity of close coordination between the raw materials (bio-based epoxy resin, bio-based polyol, and formaldehyde-free phenolic resin) and the production process in anti-deformation treatment agents for plywood to improve the performance of the anti-deformation treatment agent.

[0043] Test Example 4 The anti-deformation treatment agents prepared in Examples 1-5, Comparative Examples 1 and 4 were diluted according to the method in Test Example 2, and then the veneers were soaked in the solution. Hydrophobicity and durability tests were then conducted. The specific test method is as follows: A static drop method using a contact angle meter was used. A treated plywood sample with a smooth surface and dimensions of 50mm × 20mm was taken, and 2μL of distilled water was dropped onto the surface. The average left / right contact angle (°) was recorded. The test temperature was 25℃ and the humidity was 50%RH. Five points were measured for each sample, and the average was taken, ensuring the droplet remained stable for 10 seconds. A plywood sample measuring 150mm × 50mm × 3mm was taken, soaked in boiling water for 24 hours, and then dried at 60℃ for 2 hours. The three-point bending strength was measured using a universal testing machine at a load speed of 5mm / min. The strength retention rate (%) was calculated as (strength after soaking / initial strength) × 100. Each group was tested three times, and the average test results were taken. The final test results are shown in Table 5.

[0044] Table 5 Results of hydrophobicity and durability tests Under the conditions of Examples 1-5, the plywood treated with the prepared anti-deformation treatment agent exhibited good hydrophobicity and durability. At equilibrium ratios, fluorosilicone side chains migrated from the polyol surface, forming a low-energy layer to reduce water wetting; the epoxy-phenolic crosslinking network stabilized the cellulose structure, buffering immersion swelling; two-stage heating and a pH of 9 ensured uniform reaction and prevented microcracks. This synergy resulted in durable surface hydrophobicity and high strength retention. Under the conditions of Examples 2-4, epoxy-reinforced -OH blocking reduced water permeation channels; the high degree of phenolic polymerization provided a water-resistant scaffold; optimization of heating temperature and maintenance of a suitable alkaline environment optimized the nucleophilic rate; stable fluorine chain anchoring controlled uniform fluorine migration; good durability; and moderate hydrophobicity.

[0045] Comparative Example 1: The lack of flexible chain in the fluorosilicone resulted in an unbuffered carrier, weak surface migration, and easy hydrolysis and degradation of the highly epoxy-phenolic brittle network. After immersion, the strength decreased significantly. This defect amplified the rigidity and brittleness problem, leading to low hydrophobicity and durability, highlighting the necessity of polyol synergy. Comparative Example 4: High temperature and high pH induced side reactions that degraded the fluorine chain and cross-linking points, increasing surface energy. Rapid cooling led to easy layer separation after immersion. This harsh process resulted in network instability and the worst performance, emphasizing the key role of mild reaction conditions for durability.

[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing an anti-deformation treatment agent for plywood, characterized in that, The preparation method is as follows: bio-based epoxy resin and bio-based polyol are added to a reaction vessel, stirred and heated, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added to react and obtain the anti-deformation treatment agent precursor; chitosan solution is added to the anti-deformation treatment agent precursor, then formaldehyde-free phenolic resin is added dropwise and deionized water is added, the pH is adjusted after heating, and the reaction is carried out. After cooling and filtration, the anti-deformation treatment agent is obtained. The bio-based epoxy resin is obtained from soybean oil via an epoxidation reaction; The bio-based polyol was obtained from castor oil epoxy resin via a nucleophilic ring-opening reaction; The formaldehyde-free phenolic resin is obtained by alkaline lignin through alkaline catalytic condensation and reaction.

2. The method for preparing the anti-deformation treatment agent for plywood according to claim 1, characterized in that, The preparation method of the bio-based epoxy resin is as follows: soybean oil and formic acid are mixed to form an emulsion system, hydrogen peroxide solution and concentrated sulfuric acid are added dropwise to carry out the reaction; after cooling, the organic phase is separated and washed, dried with anhydrous sodium sulfate, and distilled under reduced pressure to obtain the bio-based epoxy resin.

3. The method for preparing the anti-deformation treatment agent for plywood according to claim 1, characterized in that, The preparation method of the bio-based polyol is as follows: the castor oil epoxy resin, the deionized water, and triethanolamine are mixed and heated and stirred to react; (tetrafluoro-1,1,2,2-tetrahydrooctyl)trihydroxysilane is added dropwise, and the reaction is continued under nitrogen protection; after cooling, the bio-based polyol is obtained by vacuum distillation.

4. The method for preparing the anti-deformation treatment agent for plywood according to claim 3, characterized in that, The (tetrazolium-1,1,2,2-tetrahydrooctyl)trihydroxysilane is obtained by dissolving (tetrazolium-1,1,2,2-tetrahydrooctyl)triethoxysilane in ethanol, followed by hydrolysis and drying under acidic conditions.

5. The method for preparing the anti-deformation treatment agent for plywood according to claim 1, characterized in that, The preparation method of the formaldehyde-free phenolic resin is as follows: the alkaline lignin and sodium hydroxide solution are mixed and stirred to dissolve, glyoxal aqueous solution is added dropwise, and the temperature is raised to react; the glyoxal aqueous solution is added, and the reaction is carried out under nitrogen protection; the mixture is cooled to obtain the formaldehyde-free phenolic resin.

6. The method for preparing the anti-deformation treatment agent for plywood according to claim 1, characterized in that, The chitosan solution is obtained by dissolving chitosan in acetic acid solution, and its addition to the anti-deformation treatment agent precursor promotes the protonation ring-opening reaction of epoxy groups and phenolic hydroxyl groups.

7. The method for preparing the anti-deformation treatment agent for plywood according to claim 1, characterized in that, In the step of adjusting pH after heating, triethanolamine is used as a pH adjuster.

8. The method for preparing the anti-deformation treatment agent for plywood according to claim 1, characterized in that, After impurities are removed by filtration using a filter membrane, the resulting anti-deformation treatment agent has a milky white appearance and a neutral pH value, which facilitates subsequent impregnation and hot-press curing.

Citation Information

Patent Citations

  • Hybrid dynamic polymer composition

    CN109666167A

  • Novel aqueous adhesives using saccharide fatty acid esters

    CN113382834A

  • Water-based formaldehyde-free adhesive as well as preparation method and application thereof

    CN113493664A

  • Epoxidized soybean oil-lignin-polybasic acid ternary adhesive and preparation method thereof

    CN118085816A

  • Hydrophobizing agents for use in making composite lignocellulose products

    US20140275351A1